Oculomotor neurorehabilitation for reading in mild traumatic brain injury (mTBI): An integrative approach. - Thiagarajan, Preethi; Ciuffreda, Kenneth J.; Capo-Aponte, Jose E.; Ludlam, Diana P.; Kapoor, Neera (NeuroRehabilitation, 2014)
BACKGROUND: Considering the extensive neural network of the oculomotor subsystems, traumatic brain injury (TBI) could affect oculomotor control and related reading dysfunction. OBJECTIVE: To evaluate comprehensively the effect of oculomotor-based vision rehabilitation (OBVR) in individuals with mTBI. METHODS: Twelve subjects with mTBI participated in a cross-over, interventional study involving oculomotor training (OMT) and sham training (ST). Each training was performed for 6 weeks, 2 sessions a week. During each training session, all three oculomotor subsystems (vergence/accommodation/version) were trained in a randomized order across sessions. All laboratory and clinical parameters were determined before and after OMT and ST. In addition, nearvision-related symptoms using the Convergence Insufficiency Symptom Survey (CISS) scale and subjective visual attention using the Visual Search and Attention Test (VSAT) were assessed. RESULTS: Following the OMT, over 80% of the abnormal parameters significantly improved. Reading rate, along with the amplitudes of vergence and accommodation, improved markedly. Saccadic eye movements demonstrated enhanced rhythmicity and accuracy. The improved reading-related oculomotor behavior was reflected in reduced symptoms and increased visual attention. None of the parameters changed with ST. CONCLUSIONS: OBVR had a strong positive effect on oculomotor control, reading rate, and overall reading ability. This oculomotor learning effect suggests considerable residual neuroplasticity following mTBI.